Sales Promotion and Impulse Buying: Investigating the Role of Hedonic Shopping Motivation in Miniso Consumers of Pasuruan - Safitri, Natalia Anggita; Oktafiah, Yuventi; Subagyo, Dyajeng Puteri Woro (Implementasi Manajemen & Kewirausahaan, 2024)
This study examines the impact of sales promotions on impulse buying behavior, mediated by hedonic shopping motivation among Miniso consumers in Pasuruan City. Sales promotions aim to boost sales by offering consumer benefits. Using a descriptive quantitative approach, this study analyzes sales promotion as an independent variable, impulse buying as a dependent variable, and hedonic shopping motivation as a mediating variable. Data were collected from 100 respondents via questionnaires and supplemented with secondary sources from journals and literature. A purposive sampling method was applied, and data analysis included outer model, inner model, and hypothesis testing using bootstrapping. The findings confirm that sales promotion significantly influences impulse buying, with hedonic shopping motivation playing a key mediating role. These results suggest that companies can enhance impulse buying by leveraging sales promotions and targeting consumers’ hedonic motivations.Keywords: Miniso, sales promotion, hedonic shopping motivation, impulse buying